Blood Biomarkers Predict Future Cognitive Decline after Military-Related Traumatic Brain Injury - Lippa, Sara M.; Gill, Jessica; Brickell, Tracey A.; Guedes, Vivian A.; French, Louis M.; Lange, Rael T. (Current Alzheimer Research, 2022)
Background: Traumatic brain injury (TBI) has been associated with an increased likelihood of late-life dementia; however, the mechanisms driving this relationship are elusive. Bloodbased biomarkers may provide insight into these mechanisms and serve as useful prognostic indicators of cognitive recovery or decline following a TBI. Objective: The aim of this study was to examine blood biomarkers within one year of TBI and explore their relationship with cognitive decline. Methods: Service members and veterans (n=224) without injury (n=77), or with a history of bodily injury (n=37), uncomplicated mild TBI (n=55), or more severe TBI (n=55), underwent a blood draw and neuropsychological assessment within one year of their injury as part of a case-control study. A subsample (n=87) completed a follow-up cognitive assessment. Results: In the more severe TBI group, baseline glial fibrillary acidic protein (p=.008) and ubiquitin C-terminal hydrolase-L1 (p=.026) were associated with processing speed at baseline, and baseline ubiquitin C-terminal hydrolase-L1 predicted change in immediate (R2Δ=.244, p=.005) and delayed memory (R2Δ=.390, p=.003) over time. In the mild TBI group, higher baseline tau predicted greater negative change in perceptual reasoning (R2Δ=.188, p=.033) and executive functioning (R2Δ=.298, p=.007); higher baseline neurofilament light predicted greater negative change in perceptual reasoning (R2Δ=.211, p=.012). Conclusion: Baseline ubiquitin C-terminal hydrolase-L1 strongly predicted memory decline in the more severe TBI group, while tau and neurofilament light strongly predicted decline in the mild TBI group. A panel including these biomarkers could be particularly helpful in identifying those at risk for future cognitive decline following TBI.
Keywords: blood biomarkers